(3GdEQTGO aj CMhGd GdUGMH Hf YHGOs - (3CMeO Hf eMeO GdMSfj GdbhHGFjs
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd GdYdeGA YdekG deG QCjJ GdUGMH GdLdjd cGai GdcaGAI GSeGYjd CfGQ Gddg eVLYI s
(3BNQgG (B:s
(3hefgG Efi bO LQHJ eQGQkG Cf GdOYGA ai HbYJg jSJLGH SQjYkG hgPG ef Cced GdahGjO s
(3HgG fXGe GdJYbjHIs
(3cKjQ ef GdYHGQGJ HGddZI GdaGQSjIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdJGQjNs